2019
DOI: 10.1021/acsami.8b18931
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-Inspired Electroactive and Antioxidative Scaffolds with Incorporation of Polydopamine-Reduced Graphene Oxide for Enhancing Skin Wound Healing

Abstract: Wound repair and tissue regeneration are complex processes that involve many physiological signals. Thus, employing novel wound dressings with potent biological activity and physiological signal response ability to accelerate wound healing is a possible solution. Herein, inspired by mussel chemistry, we developed a polydopamine (PDA)-reduced graphene oxide (pGO)-incorporated chitosan (CS) and silk fibroin (SF) (pGO-CS/SF) scaffold with good mechanical, electroactive, and antioxidative properties as an efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
153
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(157 citation statements)
references
References 63 publications
1
153
0
3
Order By: Relevance
“…Therefore, the content of silk fibroin in PVA hydrogel may be one of the factors that affect cell morphology. Although silk fibroin hydrogels are beneficial for stem cell growth and differentiation [20,21], and silk fibroin composite scaffolds are also widely studied, such as silk fibroin/chitosan/graphene oxide scaffolds [22] and silk fibroin/chitosan/bioactive glass nanoparticle scaffolds [23]. These studies indicated that the composition and content of silk fibroin in composite scaffolds play an important role in cell morphology and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the content of silk fibroin in PVA hydrogel may be one of the factors that affect cell morphology. Although silk fibroin hydrogels are beneficial for stem cell growth and differentiation [20,21], and silk fibroin composite scaffolds are also widely studied, such as silk fibroin/chitosan/graphene oxide scaffolds [22] and silk fibroin/chitosan/bioactive glass nanoparticle scaffolds [23]. These studies indicated that the composition and content of silk fibroin in composite scaffolds play an important role in cell morphology and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the fitting results of C 1s, N 1s, and O 1s of PDA-Ag-HF/GSs (Fig. 3f-h) show that the C 1s spectrum can be fitted to four peaks at 284.77, 285.94, 286.6 and 288.52 eV, corresponding to the carbon skeleton (C-C), amino group (C-N), phenolic hydroxyl group (C-OH), and carbonyl group (C=O) on PDA, respectively [24]. The peaks at 399.90 and 402.34 eV on the N 1s spectrum represent amide and the amino groups (-NH 2 ), respectively.…”
Section: Chemical Structure Of the Surface Of Gssmentioning
confidence: 95%
“…More importantly, the catechol functional group has a reducing ability and can form a redox balance [23]. Such excellent performances make DA widely used in many fields such as biomedicine [24] and the environment [18].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies showing that the application of external stimuli improves various cell behaviors and accelerates tissue regeneration among which direct current stimulation can be named [28,[33][34][35][36][37][38][39]. The use of DC has been proven to improve the proliferation of various cell types including L929.…”
Section: Electrical Properties Of the Conductive Layermentioning
confidence: 99%
“…However, the biosafety for metal oxides is higher than for metals thus to increase the conductivity of the material, they can be used in the higher dose. Obtained results showed that the nanoparticles-doped scaffolds exhibit ability to be used for cells stimulation using direct current of low voltage [28,[33][34][35][36][37][38][39]. named [28,[33][34][35][36][37][38][39].…”
Section: Electrical Properties Of the Conductive Layermentioning
confidence: 99%